Influence of pyrolysis temperature and feedstock on carbon fractions of biochar produced from pyrolysis of rice straw, pine wood, pig manure and sewage sludge. (March 2019) - Wei, Siye; Zhu, Mengbo; Fan, Xingjun; Song, Jianzhong; Peng, Ping'an; Li, Kaiming; Jia, Wanglu; Song, Haiyan
Abstract: In this study, the influences of feedstock and pyrolysis temperature on carbon fractions of biochar were investigated. Four types of organic wastes (rice straw (RS), pine wood (PW), pig manure (PM) and sewage sludge (SS)) were pyrolyzed at different temperatures (300 °C, 400 °C, 500 °C, 600 °C and 700 °C). Biochar produced at low temperature exhibited high yields, high dissolved organic carbon (DOC) content and unstable organic carbon content. In contrast, biochar formed at high temperature showed high C content and C stability with a low O/C and H/C ratios. In addition, the biochar pyrolyzed from PW contained the lowest DOC of the four biochar types. The properties of DOC fractions (F1, F2 and F3) released from biochar differed depending on feedstock, pyrolysis temperatures, and extraction procedures. The highest specific ultraviolet absorbance at 254 nm of the F1 and F2 fractions were observed for RS biochar, suggesting that more aromatic organic matter was present in sequentially extracted fractions of RS biochar than in extracts from the other biochars. In addition, the hot water extracts (F2) mostly showed higher aromaticity than cold water extracts (F1). The stability of biochars was greatly enhanced at pyrolysis temperatures >500 °C. If the biochars produced in this study were to be used for carbon sequestration in soil, the first priority should be PW, followed in order by RS and PM. Highlights: Pyrolysis temperature and feedstock affected the yield and properties of biochar. Low temperature-produced biochar exhibited a high content of DOC and unstable OC. Properties of biochar DOC differed with feedstock, temperature, and extraction. The stability of biochars was greatly enhanced at temperature exceeding 500 °C.